SOSIALISASI AKUNTANSI DAN PERPAJAKAN TENTANG WAJIB PAJAK ORANG PRIBADI BERSAMA PARA SISWA SMA PRIMA UNGGUL JAKARTA - Nugroho, Vidyarto; Melvina; Anjani, Chaterine A. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
As one of the main sources of state revenue, corporate taxes or individual taxes need to be promoted. For this reason, understanding of tax regulations and their application in practice needs to continue to be improved. PKM activities carried out together with SMA Prima Unggul partners are one effort to meet these demands. The PKM, which was carried out via zoom meeting, used interactive lecture and discussion methods. The material provided in this PKM is the definition of tax, types of tax, function of tax, taxpayers, income tax, subject and object of tax, and especially income tax for individuals and SPT which must be reported every year by individual taxpayers so that students gain insight, knowledge, and practice of individual taxpayer accounting and taxation. With this knowledge, it is hoped that students will not only calculate and report taxes correctly and on time but also have a high awareness of paying taxes. The results of this PKM show that this PKM was successful in providing understanding to students because they were enthusiastic and active in listening to the presentation of the PKM material, asking questions, and being able to answer quiz questions. In this PKM, students are reminded that, as good citizens, they need to develop awareness of paying individual taxes because the future of the nation is in their hands